Synthesis and Characterisation of Self‐Assembled and Self‐Adjuvanting Asymmetric Multi‐Epitope Lipopeptides of Ovalbumin. Issue 3 (14th November 2014) - Eskandari, Sharareh; Stephenson, Rachel J.; Fuaad, Abdullah Ahmad; Apte, Simon H.; Doolan, Denise L.; Toth, Istvan
Abstract Designing a lipopeptide (LP) vaccine with a specific asymmetric arrangement of epitopes may result in an improved display of antigens, increasing host‐cell recognition and immunogenicity. This study aimed to synthesise and characterise the physicochemical properties of a library of asymmetric LP‐based vaccine candidates that contained multiple CD4+ and CD8+ T‐cell epitopes from the model protein antigen, ovalbumin. These fully synthetic vaccine candidates were prepared by microwave‐assisted solid phase peptide synthesis. The C12 or C16 lipoamino acids were coupled to the N or C terminus of the OVA CD4 peptide epitope. The OVA CD4 LPs and OVA CD8 peptide constructs were then conjugated using azide–alkyne Huisgen cycloaddition to give multivalent synthetic vaccines. Physiochemical characterisation of these vaccines showed a tendency to self‐assemble in aqueous media. Changes in lipid length and position induced self‐assembly with significant changes to their morphology and secondary structure as shown by transmission electron microscopy and circular dichroism.